Taṭhwîr al-Mawâd al-Lughah al-‘Arâbiyyah ‘alâ Asâsi al-Wasaṭiyyah ad-Dîniyyah fî al-Jâmi’ah al-Islâmiyyah - Ani Susilawati; Nurkholis, Nurkholis; Aziz Mustofa Anwar, Abdul (Jurnal Internasional Pendidikan Bahasa Arab, 2024)
The purpose of this study is to apply the values of religious moderation through Arabic language courses in Islamic religious colleges, where this course is a type of institutional course that must be taken by all students without exception, of course this is a great opportunity for the campus to maximize efforts to prevent cases of radicalism and intolerance in the campus environment through Arabic language materials outlined in Arabic textbooks either through readings and texts related to religious norms that are tolerant, inclusive, and respectful of differences. The research method used is research on the development of a descriptive procedural model developed by Borg and Gal. The results of the study show that the development of value-based Arabic teaching materials through the four pillars of religious moderation is very important in the context of contemporary education. Materials designed with a holistic approach not only improve language proficiency, but also shape students' personalities according to the values of religious moderation. Thus, this research makes a significant contribution to Islamic education practically and theoretically and strengthening literature by adding a new dimension in the form of integrating moderation values through Arabic teaching materials.